Vaccine Hesitancy in Childhood Immunization in the Malaysian Context - Nour H. Othman; Santhanathan Rajendram; Helvinder K. Balbir Singh (Journal of Pharmacy and Bioallied Sciences)
The increase in vaccine-preventable infections in young children in Malaysia during the previous decade has been concerning. This is related to vaccine reluctance, which puts herd immunity at risk. This review evaluated the current situation and understanding of vaccine hesitancy (VH) in childhood immunization in Malaysia. A literature search was performed utilizing three databases, namely PubMed, Google Scholar, and Science Direct. The search included full-text papers published in English between January 2015 and October 2023 with specific keywords used. The narrative review included 15 articles. VH is premised on either refusal to vaccinate or delay in getting vaccination. There is a wide range of VH rates, and they differ widely by state and region. Delayed vaccination ranged from 0.03% to 21%, and refusal to vaccinate ranged from 0.08% to 42.5%. Predictors of VH include demographics, religion, lack of belief in vaccine benefits or safety, and a preference for homeopathic and complementary alternative therapies. Vaccine hesitation has recently been influenced by antivaccine propaganda and vaccine disinformation on social media. VH is an important problem that needs the attention of policymakers to avoid the recurrence of vaccine-preventable diseases. Nationwide research can help to provide a deeper understanding of the issue. Misinformation and disinformation about vaccines need to be countered. Monitoring of vaccination is necessary through a computerized registry that should be made available nationwide.